2021
DOI: 10.1186/s13287-021-02242-8
|View full text |Cite
|
Sign up to set email alerts
|

The effect of bone marrow-derived mesenchymal stem cell co-transplantation with hematopoietic stem cells on liver fibrosis alleviation and survival in patients with class III β-thalassemia major

Abstract: Background Hepatic fibrosis is a common complication in transfusion-dependent thalassemia patients. Data on the co-transplantation of mesenchymal stem cells (MSCs) with hematopoietic stem cells (HSCs) in beta-thalassemia major patients are scarce. Therefore, we aimed to evaluate the effect of co-transplantation of bone marrow-derived MSC with HSCs on the liver fibrosis alleviation and transplant outcomes in class III beta-thalassemia major. Methods … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…Various studies have demonstrated that external BMSC administration exerts effective therapeutic and protective effects on fibrotic diseases [ 35 , 36 ]. Pancreatic cancer is characterized by abundant CAFs in the stroma.…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have demonstrated that external BMSC administration exerts effective therapeutic and protective effects on fibrotic diseases [ 35 , 36 ]. Pancreatic cancer is characterized by abundant CAFs in the stroma.…”
Section: Discussionmentioning
confidence: 99%
“…This synergic crosstalk involves both direct cell-to-cell interaction and stemness signals from MSCs to HSCs and from HSCs to MSCs (Figure 3). This intrinsic relationship has been explored through the analysis of the combined effect of HSC transplantation (HSCT) with MSC [90,91] or by their combined effect in several studies to evaluate its therapeutic potential to regenerate damaged tissues [87,92,93].…”
Section: The Fascinating Potential Of Hspcs In Tissue Regenerationmentioning
confidence: 99%
“…But the most recent research showed that MSC co-transplantation with HSC or Treg is feasible, but this approach couldn’t significantly improve liver fibrosis than HSC infusion only. Robust evidence that the MSCs used to support the donor's HSCs is of recipient origin [ 13 ]. In addition, intravenous MSCs have a short lifespan and cannot migrate out of the lungs [ 14 ].…”
Section: Clinical Progress Using Stem Cells For Liver Cirrhosis/fibro...mentioning
confidence: 99%